1992
DOI: 10.1007/bf01409018
|View full text |Cite
|
Sign up to set email alerts
|

Albumin permeability and electrical resistance as means of assessing endothelial monolayer integrity in vitro

Abstract: SUMMARY:Methods were developed to measure albumin permeability and electrical resistance of bovine aortic endothelial cell (BAEC) monolayers cultured on porous polycarbonate filters. Permeability to 1% bovine serum albumin (Pe) was quantified by measuring the flux of fluorescent-labeled albumin with an apparatus in which there were no transmural oncotic or hydrostatic pressure gradients. The effect of passage of BAEC monolayers in culture on permeability was studied using 60 BAEC monolayers of Passage 6 to 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Junctions between cells continue to mature long after the cells have become confluent (Albelda et al, 1988;Sill et al, 1992;Yaccino et al, 1997;Underwood et al, 1999;Kaida et al, 2000;Penfold et al, 2000). These studies have shown that the permeability to solutes, electrical resistance, and hydraulic conductivity can continue to change one to 2 weeks post confluence in endothelial monolayers.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Junctions between cells continue to mature long after the cells have become confluent (Albelda et al, 1988;Sill et al, 1992;Yaccino et al, 1997;Underwood et al, 1999;Kaida et al, 2000;Penfold et al, 2000). These studies have shown that the permeability to solutes, electrical resistance, and hydraulic conductivity can continue to change one to 2 weeks post confluence in endothelial monolayers.…”
Section: Future Workmentioning
confidence: 99%
“…These in vitro cell layers show large (micro-sized) intercellular gaps (Underwood et al, 1999;Alvarado et al, 2004) that are not seen physiologically. The permeability of vascular monolayers are reported to be 10-100 times greater than for intact endothelia, presumably due to such defects (Albelda et al, 1988;Sill et al, 1992). Formation of large blebbing structures in the cells have also been seen when these cellular layers are perfused from the basal to apical direction (Alvarado et al, 2004), but these structures are different in size and morphological characteristics from giant vacuoles that are seen in Schlemm's canal cells from intact tissues (Bill, 1970;Johnstone and Grant, 1973;Ethier, 2002).…”
Section: Future Workmentioning
confidence: 99%
“…21 Cells were grown to confluence in DMEM (Sigma) with 10% fetal bovine serum (Biowest, Ringmer, UK), 100 U/mL penicillin, and 100 g/mL streptomycin in 95% O 2 /5% CO 2 at 37°C and were used between passages 3 and 9.…”
Section: Cell Culturementioning
confidence: 99%
“…22 Cells were plated at a density of 2.5ϫ10 5 cells/cm 2 on polycarbonate membrane Transwell filters pretreated with gelatin (5 mg/L, type A from porcine skin) and fibronectin (30 g/mL). Cells between passages 6 and 12 were used in experiments.…”
Section: Cell Culturementioning
confidence: 99%